Transferability of ginger, turmeric and large cardamom SSR primers to small cardamom (Elettaria cardamomum Maton) - Cyriac, Anu; Paul, Ritto; Prasath, D; Deepesh, P V; Nirmal babu, K; Parthasarathy, V A (Journal of Tropical Agriculture, 2016)
Small cardamom (Elettaria cardamomum Maton) of the family Zingiberaceae is an important spice crop and research is in progress to develop molecular markers to study genetic diversity and taxonomic inter-relationships in this crop. In an effort to develop a repository of molecular markers for genetic analysis of small cardamom, a set of 79 SSR (simple sequence repeat) markers reported from the related genera (Amomum subulatum, Zingiber officinale and Curcuma longa ) were screened for cross generic amplification in cardamom. The study has demonstrated the transferability of 26 SSR markers to small cardamom. When tested in a group of 20 genotypes of small cardamom, the SSR profiles were often monomorphic except for three unique polymorphic SSRs. The ginger SSR marker ZOC100 produced a variety specific banding pattern for the genotype APG10 (MB3). The genotypes were heterozygous with most of the loci tested. The total number of alleles obtained was 50 with a range of one to seven alleles per SSR locus. Multiple sequence alignment of different alleles of the marker ASM1 confirmed the presence of microsatellite motifs in the alleles and the allelic variations were due to length polymorphism of microsatellite repeats. The results indicated that cardamom genome, as it is a monotypic genus, is highly conserved with little detectable molecular variations at microsatellite regions. Furthermore, the study underlined the earlier reports which state the genetic similarity and closeness of Amomum to Elettaria.